Challenges of incorporating e-learning in medical education-a review - P., Anitha; Krishnappa, Narayana; Dhar, Ruchi (International Journal of Basic & Clinical Pharmacology, 2022)
In this modern era of electronic gadgets learning is made easy and more effective using the electronic media. E-learning is it really a boon or a burden for medical education and the educators? E-learning is defined as learning mediated by technology, such as the world wide web, internet, and multi-media, based computer applications. All peer reviewed journals articles from 2009 to 2022 that reported the challenges of implementation of the e- learning were included in the study. The search was completed by three researchers over a period of 1 month from databases like Scopus, Medline, biomedical central and Google scholar. Term used for online search was “e-learning” in medical education. The common challenges in e-learning are lack of skills, inadequate time, poor infrastructure, poor communication and negative attitude of the educators. These challenges can be overcome by developing necessary skills, adopting new tools, and by better communication and having a positive attitude. E-learning in medicine is a relatively new concept. Hence it becomes imperative that the national medical council at the policy making and enforcing level become more vigilant on the fact that whether the respective Institutions are effectively using the e-learning platform for the benefit of the students or not. Whether the institutions are effectively providing all the technologies, teacher training, teaching aids for the medical teachers or not. Finally, whether the medical teachers are receptive of the new changes and willing to make better use of e-learning for the benefit of students.